2022
DOI: 10.1016/j.ibmed.2022.100049
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial intelligence to risk stratify COVID-19 patients based on chest X-ray findings

Abstract: Background Deep learning-based radiological image analysis could facilitate use of chest x-rays as a triaging tool for COVID-19 diagnosis in resource-limited settings. This study sought to determine whether a modified commercially available deep learning algorithm (M-qXR) could risk stratify patients with suspected COVID-19 infections. Methods A dual track clinical validation study was designed to assess the clinical accuracy of M-qXR. The algorithm evaluated all Chest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Numerous researchers have employed diverse predictive indicators in their investigation of COVID-19 to evaluate the prognosis of the disease's ultimate clinical outcome. These predictive indicators comprise blood samples, electrocardiograms, imaging data (CT, XCR), respiratory parameters, clinical symptoms, and other relevant information [28][29][30][31][32][33][34][35] . The concluding indicators of the study were also varied, with a primary focus on the severity of the illness, the risk of mortality, the actual mortality rate, the length of hospitalization, and other relevant factors.…”
Section: The Implementation Of Ai In Forecasting the Medical Conditio...mentioning
confidence: 99%
“…Numerous researchers have employed diverse predictive indicators in their investigation of COVID-19 to evaluate the prognosis of the disease's ultimate clinical outcome. These predictive indicators comprise blood samples, electrocardiograms, imaging data (CT, XCR), respiratory parameters, clinical symptoms, and other relevant information [28][29][30][31][32][33][34][35] . The concluding indicators of the study were also varied, with a primary focus on the severity of the illness, the risk of mortality, the actual mortality rate, the length of hospitalization, and other relevant factors.…”
Section: The Implementation Of Ai In Forecasting the Medical Conditio...mentioning
confidence: 99%
“…Deep learning systems for analyzing chest X-rays have been developed for automating the detection of radiological signs of tuberculosis [10][11][12], pneumonia [13], COVID-19 [14,15], pneumothorax, and lung nodules [16,17]. The WHO has recently endorsed computer-aided detection (CAD) technologies for tuberculosis (TB) diagnosis in individuals aged 15 and above as a replacement for human interpreters in the assessment of digital chest radiographs for TB screening and triage [18].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical applications of qXR have undergone evaluation in prior studies, studying its generalizability across various healthcare settings and geographic locations. Globally, qXR has been employed in diagnostic pathways for tuberculosis (TB) [10][11][12]20,21], lung nodules [13,16], and COVID-19 [14], as well as in the classification of CXRs as normal or abnormal [22][23][24]. A study by Govindarajan et al [22] found that qXR improved the diagnostic accuracy and turnaround time for reporting abnormal CXRs in a prospective setting.…”
Section: Introductionmentioning
confidence: 99%